Infectious Diseases of Poverty in Children: A Tale of Two Worlds. - Hansen, Caitlin; Paintsil, Elijah (Pediatric clinics of North America, 2016)
"Infectious diseases of poverty" (IDoP) describes infectious diseases that are more prevalent among poor and vulnerable populations, namely human immunodeficiency virus (HIV) infection, tuberculosis (TB), malaria, and neglected tropical diseases (NTDs). In 2013, 190,000 children died of HIV-related causes and there were 550,000 cases and 80,000 TB deaths in children. Children under age 5 account for 78% of malaria deaths annually. NTDs remain a public health challenge in low- and middle-income countries. This article provides an overview of the major IDoP that affect children. Clinicians must be familiar with the epidemiology and clinical manifestations to ensure prompt diagnosis and treatment.